2019
DOI: 10.1590/1413-785220192706226097
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the Radial Nerve Branches for the Treatment of the Anterior Interosseous Nerve Lesion: An Anatomical Study

Abstract: Objective:This anatomical study aimed to analyze the possibility of transferring the radial nerve branches destined to the brachioradialis (BR), extensor carpi radialis longus (ECRL), extensor carpi radialis brevis (ECRB), and supinator (SM) muscles to innervate the AIN.Methods:Ten limbs from five male cadavers were prepared by intra-arterial injection of a solution of 10% glycerol and formalin.Results:The presence of only one branch to the BR muscle was noted in 7 limbs and two branches were noted in three li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In all specimens, two branches were identified emerging radially and ulnarly from the PIN to enter the supinator. In previous reports, the authors have identified, in a small percentage of dissections, a single branch emerging from the PIN, which subsequently divided to innervate the superficial and deep heads of the supinator muscle (Bertelli et al, 2009; Matavelli et al, 2019). The myelinated fiber counts averaged 401 and 398 for NS and EDC, respectively, a ratio of 1:1.…”
Section: Discussionmentioning
confidence: 99%
“…In all specimens, two branches were identified emerging radially and ulnarly from the PIN to enter the supinator. In previous reports, the authors have identified, in a small percentage of dissections, a single branch emerging from the PIN, which subsequently divided to innervate the superficial and deep heads of the supinator muscle (Bertelli et al, 2009; Matavelli et al, 2019). The myelinated fiber counts averaged 401 and 398 for NS and EDC, respectively, a ratio of 1:1.…”
Section: Discussionmentioning
confidence: 99%
“…There is consistently only one ECRB branch that arises from the radial nerve further distal to ECRL, on average 11.8 mm distal to the bicondylar line. 10,11 In our single case using BR-ECRB nerve transfer, distal to proximal internal neurolysis of the fascicle supplying ECRB from its distal branch point was needed to achieve coaptation to BR branch.…”
Section: Anatomymentioning
confidence: 98%
“…The branches to BR arise on average 58.3 mm proximal to the bicondylar line (i.e., the line between the medial and lateral epicondyles) and entered the muscle on average 40.1 mm proximal to the bicondylar line. 10 One cadaveric study found 1 to 2 BR branches (1 branch 70% of limbs, 2 branches 30% of limbs), 11 whereas another cadaveric study found 1 to 4 BR branches (1 branch 10%, 2 branches 70%, 3 branches 10%, 4 branches 10%). 10 The branches to ECRL are distal to those of the BR, arising on average 34.6 mm proximal to the bicondylar line and entering the muscle on average 8.4 mm proximal to the bicondylar line.…”
Section: Anatomymentioning
confidence: 99%
See 2 more Smart Citations